2001
DOI: 10.1074/jbc.m104612200
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of the Human Multidrug Resistance Protein 3 by Bile Salt in Human Enterocytes

Abstract: The enterohepatic circulation is essential for the maintenance of bile acids and cholesterol homeostasis. The ileal bile acid transporter on the apical membrane of enterocytes mediates the intestinal uptake of bile salts, but little is known about the bile salt secretion from the basolateral membrane of enterocytes into blood. In the basolateral membrane of enterocytes, an ATP-binding cassette transporter, multidrug resistance protein 3 (MRP3), is expressed, which has the ability to transport bile salts. We hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 43 publications
4
74
1
Order By: Relevance
“…profiling using the Affymetrix U74Av2 GeneChip array displayed reduced expression (4.3-fold) of FTF target gene mrp3 (20,34), but a strong increase in CYP7A1 mRNA levels (8.4-fold) and a slightly increased SHP mRNA level (array 1 in Table III). Northern blot analysis confirmed the CYP7A1 and SHP results (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…profiling using the Affymetrix U74Av2 GeneChip array displayed reduced expression (4.3-fold) of FTF target gene mrp3 (20,34), but a strong increase in CYP7A1 mRNA levels (8.4-fold) and a slightly increased SHP mRNA level (array 1 in Table III). Northern blot analysis confirmed the CYP7A1 and SHP results (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In FTFϩ/Ϫ liver, FTF target genes mrp3 and CYP7A1 showed opposite changes in steady-state conditions (arrays 1-3, Table III), and CYP7A1, but not mrp3, was inhibited by cholic acid feeding (array CA, Table III). Likewise, in isolated intestinal cells, bile acids activate mrp3 and deactivate ASBT, via their FTF-regulatory domains (20,21). Thus, mrp3 and CYP7A1/ASBT respond to bile acids in opposite directions, as a coherent systemic way to reduce cellular toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(A recent study showed that MRP2 is also able to transport glycocholate, but the absence of reported bile acid abnormalities in MRP2-deficient humans and rats suggests that the bile salt export pump (BSEP, SPGP) is predominately responsible for this apical activity under normal conditions (Gerloff et al, 1998;Bodo et al, 2003).) The determination that MRP3 can be induced by bile acids, at least in the context of an enterocyte cell line (Caco2), and the identification of MRP3 promoter elements that mediate bile acid induction suggest that the increased levels of bile acids consequent to cholestatic conditions may directly contribute to upregulation of the pump in hepatocytes (Inokuchi et al, 2001). It has also been speculated that MRP3 may be involved in the enterohepatic circulation of bile acids, in that the pump is localized to the basolateral surfaces of enterocytes (Rost et al, 2002), where it may mediate the transport into blood of bile acids carried into the gut by the bile and taken up across the apical surfaces of enterocytes by the ileal Nadependent bile salt transporter.…”
Section: Mrp3mentioning
confidence: 99%